Edukasi Penerapan DAGUSIBU pada Kelompok Mayarakat Galesong Baru Kecamatan Galesong Kabupaten Takalar - Sitti Rahimah; Sukriani Kursia; Tuti Handayani; Muhammad Azwar; Maria Ulfa; Ismail Ismail; Michrun Michrun; Marwati Marwati (Jurnal Abdi Masyarakat Kita, 2023)
DAGUSIBU is an educational program that invites the public to know how to get, use, store and dispose of drugs properly. The Galesong Baru community in Takalar district are used to using modern medicines and traditional medicines in treating diseases, but they do not understand how to manage the medicines they keep at home. The purpose of this extension activity is to increase the community's knowledge about the correct medicinal drugs. Activities are carried out online using the Zoom Meeting application and offline by using lecture and discussion methods. The counseling material consisted of an introduction to the meaning of DAGUSIBU, drug classification, how to use several drug dosage forms, how to store drugs and how to properly dispose of drugs. Results Outreach activities on DAGUSIBU drug education to the Galesong Baru Village community group have provided additional community knowledge about how to properly manage drugs.